Serum total antioxidant capacity prior to liver transplantation for hepatocellular carcinoma is associated with 1-year liver transplantation survival. Issue 7 (July 2018) - Lorente, Leonardo; Rodriguez, Sergio T.; Sanz, Pablo; Pérez-Cejas, Antonia; Abreu-González, Pedro; Padilla, Javier; Díaz, Dácil; González, Antonio; Martín, María M.; Jiménez, Alejandro; Cerro, Purificación; Barrera, Manuel A.
Objective: To determine whether there was an association between serum total antioxidant capacity (TAC) levels prior to in liver transplantation (LT) for hepatocellular carcinoma (HCC) and 1-year LT mortality. Methods: This observational retrospective single-centre study of patients with LT for HCC measured serum levels of TAC and malondialdehyde (as a biomarker of lipid peroxidation) before LT. The study endpoint was 1-year LT mortality. Results: This study included 142 patients who underwent LT for HCC. Patients who survived the first year ( n = 127) had significantly lower aged liver donors, significantly higher serum TAC levels, and significantly lower serum malondialdehyde levels compared with the non-survivors ( n = 15). Logistic regression analysis found that serum TAC levels (odds ratio [OR] 0.275; 95% confidence interval [CI] 0.135, 0.562) and the age of the LT donor (OR 1.050; 95% CI 1.009, 1.094) were associated with 1-year LT mortality. There was an inverse association between serum levels of TAC and malondialdehyde levels (rho = –0.22). Conclusions: There was an association between low serum TAC levels prior to LT for HCC and mortality during the first year after LT. There was an inverse association between serum TAC levels and lipid peroxidation as measured by malondialdehyde levels.